HUMAN POTENTIAL IN THE PART OF THE DEFENSE ECONOMY STATE - Syzov, A.; Koval, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The issue of human potential development as one of the main sources of human capital and intellectual work in the field of defense of the country and in the country as a whole is studied. The problems of loss of human potential at the stages of its creation by analyzing the socio-economic and military situation in Ukraine, including demographic changes, changes in gross domestic product, income inequality in comparison with some European countries, the principles of personnel policy in the Armed Forces of Ukraine, management and defense spending in terms of the share of the state budget in the field of defense. The results of the analysis indicate a high level of inequality among the population of Ukraine, low purchasing power, the fact that there is a large arrears of wages, which negatively affects the ability to reproduce human abilities, as well as problems with compliance with international norms and practices. defense. An imbalance in the income of the population between the poor and rich classes, as well as the absence of the middle class. It is determined that it is expedient to create a favorable investment climate for the citizens of Ukraine, change the model of socio-economic development for the use of human capital, development of science and innovation, attract foreign investment, support national producers, preserve and create new jobs, carry out educational reform. scientific specialties that will be relevant in the future, taking into account technological progress, combating income inequality, creating a "middle class", and providing opportunities for citizens to receive a decent reward for honest work. Despite the significant growth of economic indicators, Ukraine is still characterized by a high level of poverty. This problem is solved in developed countries through adequate and effective state policy in the field of economic security, support of the national producer, creation of favorable conditions for investment processes, jobs, ensuring adequate financial support in the field of health, education and science.
Keywords: human potential, military potential, gross domestic product, economic security economic security, human capital